AN INVESTIGATION OF THE EFFECTS OF EARLY MALADAPTIVE SCHEMAS ON PRE-COUNSELLING AND TRAIT ANXIETY LEVELS OF PSYCHOLOGICAL COUNSELORS AND COUNSELLING TRAINEES - Hatice Deniz GÜNAYDIN (Fırat University, 2020)
The aim of this study is to investigate the effect of early period maladaptive schemas on pre-counselling and continuous anxiety levels of psychological counselors and counselling trainees. The study group consisted of 436 people , 233 of whom are psychological counselors having worked in various schools in the center of Konya in 2012-2013 academic year , and 202 of whom are Psychological Counseling and Guidance Department students in Necmettin Erbakan University Ahmet Keleşoğlu Faculty. In the study, “Young Schema Scale Short Form 3 ”has been used to determine early maladaptive schema scores , “State and Trait Anxiety Inventory” has been used to determine the pre-consultative and trait anxiety scores ; and Personal Information Form prepared by the researcher has been used to determine the information about gender and age. According to the results of the research, except for emotional deprivation, emotional inhibition, defectiveness and self-sacrifice , all early maladaptive schemas (failure to achieve, pessimism, social isolation, approval- seeking, enmeshment, entitlement, abandonment, punitiveness, vulnerability to harm or illness , unrelenting standards ) of the Psychological Counselors have been found to be significantly correlated with state anxiety levels. All 18 early maladaptive schemas of psychological counselors have been found to be significantly correlated with trait anxiety levels. As for the counselling trainees, except for their emotional deprivation, entitlement, and unrelenting standards , all early maladaptive schemas (failure to achieve, pessimism, social isolation, emotional inhibition, approval- seeking, enmeshment, entitlement, self-sacrifice , abandonment, punitiveness, defectiveness, vulnerability to harm or illness ) have been found to be significantly correlated with state anxiety levels.Except for self-sacrifice , punitiveness, all early maladaptive schemas ( emotional deprivation, failure to achieve, pessimism, social isolation, emotional inhibition, approval- seeking, enmeshment, entitlement, abandonment, vulnerability to harm or illness , unrelenting standards ) of the counselling trainees have been found to be positively and significantly correlated with trait anxiety levels.